Prediction and control of drop formation modes in microfluidic generation of double emulsions by single-step emulsification - Nabavi, Seyed Ali; Vladisavljevic, Goran T.; Bandulasena, Monalie V.; Arjmandi-Tash, Omid; Manovic, Vasilije (Elsevier, 2017)
Hypothesis Predicting formation mode of double emulsion drops in microfluidic emulsification is crucial for controlling the drop size and morphology. Experiments and modelling A three-phase Volume of Fluid-Continuum Surface Force (VOF–CSF) model was developed, validated with analytical solutions, and used to investigate drop formation in different regimes. Experimental investigations were done using a glue-free demountable glass capillary device with a true axisymmetric geometry, capable of readjusting the distance between the two inner capillaries during operation. Findings A non-dimensional parameter (ζζ) for prediction of double emulsion formation mode as a function of the capillary numbers of all fluids and device geometry was developed and its critical values were determined using simulation and experimental data. At logζlogζ > 5.7, drops were formed in dripping mode; the widening jetting occurred at 5 < logζlogζ < 5.7; while the narrowing jetting was observed at logζlogζ < 5. The ζζ criterion was correlated with the ratio of the breakup length to drop diameter. The transition from widening to narrowing jetting was achieved by increasing the outer fluid flow rate at the high capillary number of the inner fluid. The drop size was reduced by reducing the distance between the two inner capillaries and the minimum drop size was achieved when the distance between the capillaries was zero.
Keywords: Droplet microfluidics; Dripping regime; Narrowing jetting; Widening jetting; Core-shell droplets; Double emulsions; Dripping-to-jetting transition; Velocity profile; Volume of Fluid–Continuum Surface Force model; glass capillary device